ARGUMENTS SKILLS ENHANCEMENT THROUGH THE IMPLEMENTATION OF PROBLEM BASED LEARNING IN 10th GRADE STUDENTS OF MIA 1 SMA BATIK 2 SURAKARTA - Pritasari, A. C.; Dwiastuti, S.; Probosari, R. M.; Sajidan, S. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2015)
This research was aimed to improve the studentsâ€™ argumentation skill in X MIA 1 SMA Batik 2 Surakarta Academic Year 2014/2015 through the implementation of problem based learning. This research is a classroom action research which consisted of three cycles. Each cycle contained planning, acting, observing and reflecting. The subjects of this research were students in X MIA 1 of SMAÂ Batik 2 Surakarta Academic Year 2014/2015. The data was collected using test, interview, and documentation. The data validation used triangulation technic. The data were analyzed descriptive was based on three components, they are: data reduction, data presentation and drawing the conclusion or verification. The research procedure is using spiral method. The results showed that argumentation skill of students increase from pre cycle, cycle I, cycle II, and cycle III. The average of studentsâ€™ argumentation skill increase from 28,96% to 50,06%. Claim aspect increase from 61,62% to 82,49%; evidence aspect increase from 15,66% to 37,37%; and reasoning aspect increase from 9,60% to 30,30%. Based on the result of the research, the conclusion is there are improvement of argumentation skill through implementation of problem based learning in X MIA 1 SMA Batik 2 Surakarta.